Study on the Oxidation Resistance of Cr20Ni80 Electrothermal Alloy Wire by Aluminized Coating - WANG Xiao-jun, WANG Xin (Cailiao Baohu)
In order to improve the high-temperature oxidation resistance of electrothermal alloy wire, an aluminized coating was prepared on the surface of Cr20Ni80 electrothermal alloy wire by solid powder embedding.The high-temperature oxidation test of aluminized sample was carried out at 1 000 ℃ in air by a high resistance heating electrothermal alloy fast life device, and the fast life test was performed at a constant temperature of 1 200 ℃ with fitting the resistance curve with time.In addition, X-ray diffraction(XRD), scanning electron microscope(SEM), energy spectrum analysis(EDS)and thermogravimetric analyzer(TGA)were used to study the structure of aluminized coating, the morphology and phase composition of oxide films and the oxidation kinetics of aluminized sample.Results showed that the fast life of aluminized samples increased by 7.62% compared with that of unaluminized samples.The aluminized coating possessed a two-layer structure with 5 μm thickness of the inner layer and 40 μm thickness of the outer layer.Meanwhile, the oxidation kinetics curve of the aluminized sample basically conformed to the parabolic law.The oxide film could be divided into three layers: the outermost layer was Al2O3 and trace NiO; the secondary outer layer was NiAl and a small amount of Al2O3 and NiO; the innermost layer was Cr-rich layer, Cr2O3 and a small amount of SiO2 with discontinuous distribution.At the initial stage of oxidation, an uniform and dense Al2O3 protective oxide film was formed quickly on the surface of aluminized sample, so that the oxidation resistance of Cr20Ni80 electrothermal alloy wire was effectively improved.